Analysis of the School Environment, Teacher Communication and Student Learning Motivation on the Influence of Student Learning Outcomes - Benar Sembiring; Harbeng Masni; Arif Rahim; Erlina Zahar; Zuhri Saputra Hutabarat; Firman Tara; Ria Agustina; Sujoko Sujoko; Rahmawati Rahmawati; Lili Andriani (International Journal of Multidisciplinary Sciences and Arts, 2024)
Research Objectives: 1) To partially analyze the influence of the school environment on student learning achievement; 2) To partially analyze the influence of teacher communication on student learning achievement; 3) To analyze the influence of student learning motivation on student learning achievement partially; and 4) To analyze the influence of the school environment, teacher communication and learning motivation on student learning achievement simultaneously. This research is included in the associative causality group. It is classified as associative because this research aims to determine whether or not there is a relationship between the variables being studied. It is categorized as causality, because this research aims to find out whether the observed variables have a certain causal relationship as predicted theoretically. The method used is a quantitative method. The results of this research conclude: 1) the school environment has a partial influence on student learning achievement; 2) teacher communication has a partial influence on student learning achievement; 3) student learning motivation has a partial influence on student learning achievement; 4) the school environment, teacher communication, and student learning motivation have an influence on student learning achievement simultaneously.